Tracing the evolutionary history of the mole, Talpa europaea, through mitochondrial DNA phylogeography and species distribution modelling. (March 2015) - Feuda, Roberto; Bannikova, Anna A.; Zemlemerova, Elena D.; Di Febbraro, Mirko; Loy, Anna; Hutterer, Rainer; Aloise, Gaetano; Zykov, Alexander E.; Annesi, Flavia; Colangelo, Paolo
<x xml:space="preserve">Abstract</x> Our understanding of the effect of Pleistocene climatic changes on the biodiversity of European mammals mostly comes from phylogeographical studies of non‐subterranean mammals, whereas the influence of glaciation cycles on subterranean mammals has received little attention. The lack of data raises the question of how and to what extent the current amount and distribution of genetic variation in subterranean mammals is the result of Pleistocene range contractions/expansions. The common mole (Talpa europaea) is a strictly subterranean mammal, widespread across Europe, and represents one of the best candidates for studying the influence of Quaternary climatic oscillation on subterranean mammals. Cytochrome b sequences, as obtained from a sampling covering the majority of the distribution area, were used to evaluate whether Pleistocene climate change influenced the evolution of T. europaea and left a trace in the genetic diversity comparable to that observed in non‐subterranean small mammals. Subsequently, we investigated the occurrence of glacial refugia by comparing the results of phylogeographical analysis with species distribution modelling. We found three differentiated mitochondrial DNA lineages: two restricted to Spain and Italy and a third that was widespread across Europe. Phylogenetic inferences and the molecular clock suggest that the Spanish moles represent a highly divergent and ancient lineage, highlighting for the first time the paraphyly of T. europaea. Furthermore, our analyses suggest that the genetic break between the Italian and the European lineages predates the last glacial phase. Historical demography and spatial principal component analysis further suggest that the Last Glacial Maximum left a signature both in the Italian and in the European lineages. Genetic data combined with species distribution models support the presence of at least three putative glacial refugia in southern Europe (France, Balkan Peninsula and Black Sea) during thelast glacial maximum that likely contributed to post‐glacial recolonization of Europe. By contrast, the Italian lineage remained trapped in the Italian peninsula and, according to the pattern observed in other subterranean mammals, did not contribute to the recolonization of northern latitudes. © 2015 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 495–512.